2021
DOI: 10.1097/nne.0000000000001110
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Teamwork in Schools of Nursing

Abstract: Background: Characteristics of high-performing teams include shared purpose, clear vision, strong leadership, and the ability to use conflict management when needed. While many individuals who teach in schools of nursing come from the clinical setting where teamwork is normative, that same expectation of teamwork may not be present for the faculty as a whole. Purpose: This study assessed perceptions of teamwork among faculty members in schools of nursing in 4 states in the Midwestern region of the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Teamwork is essential in any profession where people come together to achieve a common goal. Characteristics of a high-performing team include shared purpose, clear vision, strong leadership, and the ability to manage conflict when needed (Cooke & Valentine, 2022). Clinical settings rely on effective teamwork, as it has been found to enhance interdisciplinary collaboration and improve quality outcomes for patients (Salas, Zajac & Marlow, 2018).…”
Section: Teamworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Teamwork is essential in any profession where people come together to achieve a common goal. Characteristics of a high-performing team include shared purpose, clear vision, strong leadership, and the ability to manage conflict when needed (Cooke & Valentine, 2022). Clinical settings rely on effective teamwork, as it has been found to enhance interdisciplinary collaboration and improve quality outcomes for patients (Salas, Zajac & Marlow, 2018).…”
Section: Teamworkmentioning
confidence: 99%
“…Looking outside the midwifery profession, a recent study on the perceptions of teamwork in schools of nursing found a similar theme. Reporting that elements of positive teamwork which included communication, support, situation monitoring, and leadership if present, all resulted in job satisfaction, workforce retention, and reduced turnover of staff (Cooke & Valentine, 2022).…”
Section: Teamworkmentioning
confidence: 99%